Insulin like growth factor 2 mRNA binding protein 2 regulates vascular development in cerebral arteriovenous malformations - Wang, Lin-jian; Wu, Yangyang; Xie, Sha; Lian, Hongkai (Frontiers in Neurology, 2024)
BackgroundCerebral arteriovenous malformations (AVMs) are intricate vascular anomalies that disrupt normal cerebral blood flow, potentially leading to severe neurological complications. Although the pathology of AVMs is not fully understood, epigenetic mechanisms have been implicated in their formation.MethodsTranscriptional differences between cerebral AVMs and normal tissues were analyzed using RNA sequencing (RNA-seq), identifying IGF2BP2 as a key differentially expressed gene. Comprehensive bioinformatics analysis, integrating multi-omics data such as RNA-seq and methylated RNA immunoprecipitation sequencing (MeRIP-seq), was employed to identify the downstream target gene of IGF2BP2. The roles of specific genes in vascular development were assessed using endothelial cell cultures and zebrafish models.ResultsOur analysis of RNA-seq data from cerebral AVMs and normal tissues identified IGF2BP2, a key N6-methyladenosine (m6A) reader, as significantly downregulated in cerebral AVMs. Functional studies showed that IGF2BP2 knockdown resulted in abnormal angiogenesis in endothelial cells and disrupted vascular development in zebrafish models. Mechanistically, IGF2BP2 regulates LGALS8 expression by modulating mRNA stability through m6A modification, and LGALS8 deficiency severely impairs angiogenesis in vitro and leads to cerebrovascular dysplasia in vivo.ConclusionOur findings suggest that IGF2BP2, via m6A-dependent regulation of LGALS8, is crucial for vascular development and presents potential targets for therapeutic intervention in cerebral AVMs.